Features of teaching Chemistry in English: continuity of traditional and new technologies - Nurdillayeva, R.N.; Baisalova, A.Zh.; Zhuman, G.O. (KSU Publ., 2020)
The article describes the study results of the continuity of traditional and new technologies in teaching chemistry in English in secondary schools. In the study, alongside a variety of traditional methods, the CLIL method, Content and Language Integrated Learning was explored to enhance pupils' interest in chemistry and to improve their knowledge. Special attention was drawn to the learners' motivation, knowledge level and English language proficiency during the study of chemistry. The ways to apply new approaches towards teaching chemistry in English were considered and the practice of integrating chemistry and English on the basis of a new curriculum was studied. Terminology, glossary, English language-based text work and calculation methodology were selected for the classroom use of CLIL technology. At chemistry lesson pupils were surveyed and a pedagogical observation was performed to determine the effectiveness of using CLIL technology. According to the survey results the effectiveness of teaching chemistry in English was proven. Working on terminology and glossary the learners’ interest in the subject was increased by using chemistry terminology in the classroom. The use of CLIL approach is based on integrating language in teaching the subject content allowed the pupils not only to gain information about the subject but also to master the language.
Химияны ағылшын тілінде оқытудың ерекшелігі: дәстүрлі және жаңа технология сабақтастығы
Особенности преподавания химии на английском языке: преемственность традиционных и новых технологий
Keywords: CLIL method; teaching chemistry in English; Content and Language Integrated Learning; glossary; terminology; English language based text; CLIL technology; a survey; traditional method